Uncovering the role of Rad51 in homologous recombination-mediated antigenic diversification in the human malaria parasite Plasmodium falciparum - Vydyam, Pratap; Roy, Nabamita; Bhattacharyya, Mrinal Kanti (Frontiers in Molecular Biosciences, 2023)
The human malaria parasite Plasmodium falciparum maintains chronicity of infection through antigenic variation, a well-coordinated immune evasion mechanism. The most prominent molecular determinant of antigenic variation in this parasite includes the members of the var multi-gene family. Homologous recombination (HR) mediated genomic rearrangements have been implicated to play major role in var-gene diversification. However, the key molecular factors involved in generation of diversity at var loci is less known. Here we have tested the hypothesis that PfRad51 could carry out recombination between var genes that are not homologous, but homeologous in nature. We employed whole-genome-sequencing (WGS) approach to investigate recombination events among var sequences over one-hundred generations, and compared the rate of sequence-rearrangement at the var loci in both PfRad51 proficient and deficient parasite lines. This brief report provides evidence that the loss of the key recombinase function renders parasite HR deficient, and results in fewer recombination events among the var-sequences, thereby impacting the diversification of var-gene repertoire.